Інформаційно-аналітичне забезпечення оперативно-розшукової діяльності щодо протидії тероризму - Лисенко, Андрій Миколайович; Лисенко, Ірина В'ячеславівна; Перевалова, Людмила Вікторівна (Луганський державний університет внутрішніх справ ім. Е. О. Дідоренка, 2019)
У даній науковій статті розглядаються зміст та сутність інформаційно-аналітичного забезпечення оперативно-розшукової діяльності щодо протидії тероризму з метою виявлення існуючих недоліків у цій сфері. Під час дослідження були використані результати аналізу опрацьованої спеціальної фахової літератури, законодавчих актів, практичного досвіду протидії злочинам, пов’язаних із тероризмом та особистого досвіду роботи в правоохоронних органах. Автори надали науково-обґрунтовані пропозиції щодо удосконалення інформаційно-аналітичного забезпечення зазначеної діяльності.

In the article, based on a comprehensive analysis of professional literature, practical experience of information and analytical support of operative and investigative activities in the field of counter-terrorism, the inherent disadvantages are highlighted and the ways of their solution are offered. The effectiveness of countering terrorism depends on the level of awareness of the operational units' employees about the existing criminal proceedings. Without a sufficient amount of information, the counteraction to terrorism will be nonsystematic, accidental in nature. However, in practice there are significant shortcomings in the organization of information and analytical support for counter-terrorism, namely: the failure of individual operational workers to receive current operational information on the preparation of these crimes and those involved, to determine the sources of probable information, the inability to make the correct assessment get the information and use it in the most effective way. The authors propose to solve these disadvantages by using administrative levers and taking measures for: 1) maintain the staff of the operational units, especially those with experience of practical activity for more than 5 years, and the creation of appropriate working conditions for this purpose, because the absence of experienced workers is negatively reflected in the training of new operational staff, which in the future leads to a decrease in the quality of information and analytical support their operational and investigative activities; 2) increase the level of initial professional training of operational units and the training of students in higher education institutions with specific learning conditions, by attracting experienced apprentices of operational units to work at applied departments, with the purpose of studying experience, mastering skills and skills of carrying out informational and analytical support operatively -development activities; 3) changes in the system of criteria for evaluating the operations of operational units by replacing the quantitative indicators of the revealed crimes on the assessment of the prevalence of crimes in the area of operational service, in order to reduce the burden on operational staff, which will enable them to focus on the quality of information and analytical support for their activities.
Information and analytical support of operational-search activity on counteraction to terrorism
Keywords: джерела; терористична діяльність; кримінальні процеси; СБУ; правоохоронні органи; information and analytical support; operative-search information; sources of operative-search information; operative-search activity; terrorism